4D PET/CT as a Strategy to Reduce Respiratory Motion Artifacts in FDG-PET/CT - Chi, Alexander; Nguyen, Nam P. (Frontiers in Oncology, 2014)
The improved accuracy in tumor identification with FDG-PET has led to its increased utilization in target volume delineation for radiotherapy treatment planning in the treatment of lung cancer. However, PET/CT has constantly been influenced by respiratory motion-related image degradation, which is especially prominent for small lung tumors in the peri-diaphragmatic regions of the thorax. Here, we describe the current findings on respiratory motion-related image degradation in PET/CT, which may bring uncertainties to target volume delineation for image guided radiotherapy (IGRT) for lung cancer. Furthermore, we describe the evidence suggesting 4D PET/CT to be one strategy to minimize the impact of respiratory motion-related image degradation on tumor target delineation for thoracic IGRT. This, in our opinion, warrants further investigation in future IGRT-based lung cancer trials.